Exploring the Nexus between social media and online shopping: a Malaysian consumer perspective with an emphasis on Islamic ethics - Ramli, Mohd Safwan; Ayob, Nur Hidayah; Ramdzan Ali, Al Amirul Eimer; Abdullah, Nur Nabilah; Yaacob, Noor Junaini Arwin; Mohd Basari, Shahrul Nizam (2024)
This research investigates the influence of social media dynamics on the online purchase intentions of Malaysian consumers, employing the Theory of Planned Behavior. It examines the relationship between social media attributes such as community sense, usefulness, openness, participation, and accessibility, and the propensity to make online purchases. Through a comprehensive Pearson Correlation analysis, the study identifies a strong positive correlation between these social media characteristics and purchase intentions. Additionally, the research highlights the significant impact of attitude, particularly when shaped by Islamic ethics, on purchasing decisions. The findings suggest that optimizing specific social media elements can enhance consumer engagement and conversion rates in Malaysia, while also enriching theoretical discussions by integrating cultural and ethical dimensions into models of online consumer behavior (Ranawi et al., 2019; Peña-García et al., 2020).